Parting Words : Victorian Poetry and Public Address - Sider, Justin, 1982- (Book collections on Project MUSE., 2018)
"Parting Words examines the relationship between Victorian poetry and public culture through the lens of the valedictory or farewell address, considering works ranging from poems by Byron, Tennyson, and Browning, to essays by Twain and Wilde, to scenes from novels by Dickens and Eliot. Ironically, the Victorian demand for a public poetry was countered by a growing diversification of that public. Although the Victorian era saw the loss of faith in a unitary national public, it asked poetry to address just such a public. It is in tackling this contradiction that the Victorian poets negotiated the reception of their work"--